Kualitas Fisik Tepung Putih Telur Gagal Tetas dengan Penambahan Ragi Tape - Fadhila, Natasya (Buletin Peternakan Tropis, 2023)
ABSTRACT The purpose of this study was to evaluate the physical quality of failed hatching egg albumen flour (TPTGT) which has been added with yeast tape with different concentrations. Five treatments and 4 replications were arranged in a randomized block design (RBD). The treatment in this study consisted of TPTGT without the addition of tape yeast (P0) and TPTGT with the addition of tape yeast (0.25%, 0.50%, 0.75%, and 1%) for treatments P1, P2, P3 and P4 respectively. The pH value, yield, water content, and foaming power were observed in this study. Data were statistically analyzed using ANOVA. If the ANOVA has a significant effect then it is continued with Duncan's multiple range test. The results showed that the pH value, yield, water content and foaming percentage of albumen flour for failed hatching eggs had no significant effect (P>0.05) due to the addition of tape yeast at different levels. The range of pH values ​​obtained was 6.93 – 7.43, the yield value was 15.10% - 16.41%, the water content was 12% - 15% and the foaming power was 120% - 140%. The pH value of TPTGT with the addition of up to 1% tape yeast is within the quality value range required by SNI, but the addition of up to 1% tape yeast has not been able to reduce the water content, increase the foaming power and yield of TPTGT. Keywords: egg albumen flour, failed hatching eggs, physical quality, tape yeast. ABSTRAK Tujuan dari penelitian ini adalah untuk mengevaluasi kualitas fisik tepung putih telur gagal tetas (TPTGT) dengan penambahan ragi tape. Penelitian terdiri atas 5 perlakuan, masing-masing perlakuan dibagi ke dalam 4 kelompok (RAK)  Perlakuan terdiri atas P0 (TPTGT tanpa penambahan ragi tape 0%), P1 (TPTGT dengan penambahan ragi tape 0,25%), P2  (TPTGT dengan penambahan ragi tape 0,50%), P3 (TPTGT dengan penambahan ragi tape 0,75%) dan P4 (TPTGT dengan penambahan tape 1%). Peubah yang diamati adalah pH, rendemen, kadar air, dan daya buih. Data dianalisis menggunakan ANOVA, jika analisis ragam berpengaruh nyata maka dilanjutkan dengan uji jarak berganda Duncan. Hasil penelitian menunjukkan penambahan ragi tape dengan konsentrasi yang berbeda berpengaruh tidak nyata (P>0,05) terhadap nilai pH, rendemen, kadar air dan daya buih tepung putih telur gagal tetas. Kisaran nilai pH yang diperoleh adalah 6,93 – 7,43, nilai rendemen 15,10% - 16,41%, kadar air 12% - 15% dan daya buih 120% - 140%. Nilai pH TPTGT dengan penambahan ragi tape sampai 1% berada dalam kisaran nilai mutu yang disyaratkan SNI, tetapi penambahan ragi tape sampai 1 % belum mampu menurunkan kadar air, meningkatkan daya buih dan rendemen TPTGT. Kata kunci : kualitas fisik, ragi tape, telur gagal tetas, tepung.